Effects of Stair Climbing Training on Cardiopulmonary Endurance in Gym Users - Nadia Anwer, SumaiyahObaid, HanifaSuleman, AimanNiaz, Attiq Ur Rehman, Shaher Bano, Arslan Saleem, Sufian Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Stair climbing is an effective, easy to approach and inexpensive moderate to high intensity exercise with great effects in improving functional status of individuals.High intensity interval training (HIIT) protocol is also a short time exercise with greater long term effects in improving cardiopulmonary endurance. Aim: To examine the effects of stair climbing on cardiopulmonary endurance in gym users in addition to High intensity interval training (HIIT) protocol and to measure the effects of stair climbing on blood lactate in gym users. Methods: 32 healthy individuals including males and females have been divided into two groups all the participants were gym users from past three months .Control group followed HITT protocol only and experimental group performed stair climbing in addition to HIIT protocol. Time duration of the training was 8 weeks .Individuals were assessed before and after the training for VO2max, and blood lactate. Body Mass Index, Rate of Perceived Exertion, and O2cost, modified Canadian Aerobic Fitness Test (mCAFT) stages Blood Pressure, Heart Rate has also been assessed before and after training. Results: Results has shown the significant increase in VO2 max (p value 0.001) and lower levels of blood lactate (≤0.001) within the groups after training. There was no significant improvement in VO2max and blood lactate formation on comparison between the groups. Conclusion: Current study concluded that there was significant increase in VO2 max and blood lactate with stair climbing in addition to HIIT protocol in gym users within the groups but there is no significance between the groups. It means both the protocols been followed are significant with almost equal affects and both are equally beneficial.